The school leader's year month-by-month progress, every lesson, every day - Harpham, Michael (Routledge, Taylor & Francis Group, 2022)
"This practical handbook offers a month-by-month guide to the curriculum, assessment, progress and leadership over the school year. It provides a clear, comprehensive, and coherent structure to the academic year helping school leaders to prioritise their time and workload, supporting them and their team to work as efficiently and effectively as possible. Considering the statutory and key leadership activities from admissions, induction, transitions and parents' evenings to coursework, timetabling, assessment, staff performance and much more, the book provides a clear plan of action to ensure school leaders have prepared their work at the optimal time over the year. Each chapter features tried and tested strategies to help schools put robust systems and processes in place alongside guidance on sustaining pace, developing resilience and exam preparation and technique. Full of practical tips to help improve progress and including real world examples of leadership in action from leaders working in primary and secondary schools, this is essential reading for all school leaders that want their their students to be as successful as they can possibly be in every lesson, every day"--